Anti-Inflammatory Effects and Human Skin Safety of the Eastern Traditional Herb Mosla japonica - Hyun-Ju Han; Chang-Gu Hyun (Life)
Traditional knowledge has long provided natural solutions for disease prevention and treatment, complementing modern medicine. Mosla japonica (Korean mint) has been traditionally valued for its pesticidal, dehumidifying, anti-swelling, and detoxifying properties. This study explores its anti-inflammatory potential using M. japonica extract (MJE) in LPS-stimulated RAW 264.7 macrophages and evaluates its safety for human skin applications. MJE significantly reduced inflammatory mediators such as nitric oxide (NO), prostaglandin E2 (PGE2), and key cytokines (IL-1β, IL-6, TNF-α) in a dose-dependent manner. It also suppressed the expression of iNOS and COX-2, enzymes crucial for inflammation. Mechanistically, MJE inhibited NF-κB activation by stabilizing IκBα, thereby reducing inflammation-related gene expression. Additionally, it downregulated ERK, JNK, and p38 in the MAPK signaling pathway, further contributing to its anti-inflammatory effects. A primary skin irritation test confirmed MJE’s safety, showing no significant skin reactions at 100 μg/mL. These findings highlight MJE’s strong anti-inflammatory properties and potential for dermatological applications. This study underscores the pharmacological value of M. japonica and its integration into modern scientific research, aligning with global biodiversity frameworks such as the Nagoya Protocol. Future research may further expand its applications in medicine and skincare.